"The west African Ebola disaster has stretched us to near breaking point": MSF's volunteer doctors need your support. (3rd December 2014) - Godlee, Fiona
Abstract : Médecins Sans Frontières is bringing much needed medical personnel to west Africa to help with the current Ebola outbreak, writes Fiona Godlee . The charity has decades of experience in bringing volunteer doctors to where they are needed in a crisis and in ongoing humanitarian projects all over the world, which is why we've chosen MSF for The BMJ 's Christmas appeal this year. Please give generously